2019
DOI: 10.1002/jcph.1358
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics, Safety, and Tolerability of Single‐Dose Intravenous Moxifloxacin in Pediatric Patients: Dose Optimization in a Phase 1 Study

Abstract: The pharmacokinetics, safety, and tolerability of a single dose of moxifloxacin were characterized in 31 pediatric patients already receiving antibiotics for a suspected or proven infection in an open-label phase 1 study. A dosing strategy for each age cohort (Cohort 1: ࣙ6 years to ࣘ14 years; Cohort 2: ࣙ2 years to <6 years; Cohort 3: >3 month to <2 years) was developed using physiology-based pharmacokinetic modeling combined with a stepwise dosing scheme to obtain a similar exposure to adults receiving 400 mg … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 36 publications
1
23
0
Order By: Relevance
“…administered moxifloxacin in children of different ages. Based on the known pharmacological profile of moxifloxacin and a therapeutic target range established in adults, an age‐dependent dosing scheme for moxifloxacin could be proposed (learning step) and tested in the first‐in‐children trial . The analysis of the uncertainties associated with model‐based predictions using phase I results as a reference resulted in refined doses that were confirmed in the larger phase III study investigating moxifloxacin treatment for cIAIs in children .…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…administered moxifloxacin in children of different ages. Based on the known pharmacological profile of moxifloxacin and a therapeutic target range established in adults, an age‐dependent dosing scheme for moxifloxacin could be proposed (learning step) and tested in the first‐in‐children trial . The analysis of the uncertainties associated with model‐based predictions using phase I results as a reference resulted in refined doses that were confirmed in the larger phase III study investigating moxifloxacin treatment for cIAIs in children .…”
Section: Discussionmentioning
confidence: 98%
“…During conduction of the phase I and III studies, these dose recommendations were subject to clinical validation and assessment through independent safety boards, allowing for the adjustment of the recommended doses if deemed necessary. The details of the clinical dose adjustment steps are presented in the clinical papers describing the phase I and III trials of moxifloxacin in children …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Figure shows the single‐dose exposure (expressed as area under the concentration‐time curve [AUC]) predicted for children with a PBPK model in comparison to the data observed in the first clinical trial with rivaroxaban in children . Another example is the fluoroquinolone antibiotic moxifloxacin the clearance of which was predicted in children by PBPK modeling before the conduction of pediatric trials and compared with individual data observed in 2 pediatric trials . In both case examples, PBPK modeling in children using previous ontogeny information has been proven to be very helpful to guide the development of suitable dosing regimens in pediatric development programs.…”
Section: Application Of Pbpk In Pediatric Researchmentioning
confidence: 99%